Variação temporal do fator de perda de carga em sistemas fluido mecânicos provocada pela bioincrustação do mexilhão dourado : um estudo de caso - Tâmara Rita Costa de Souza (2023)
Pumping systems, mainly those used in the water supply sector and in industrial and hydroelectric facilities, are commonly infested by the golden mussel. This causes an increase in maintenance operations (for example, system shutdowns for cleaning) which can lead to an increase in energy costs. The geographic expansion of the golden mussel in Latin America presents an economic risk, not only for the ecosystem in general, but also for the energy sector. The imminence of its spread in the Amazon, one of the main river basins in South America, is a matter of concern due to the problems that the bioinvasion of this species can cause. Given the lack of studies on the loss of energy efficiency in pumping systems impacted by the golden mussel, this study proposes a methodology to estimate the increase in energy consumption and pumping cost caused by bioinfestation. For the standardization of methods and development of calculations (new equations), evaluations of the available literature (on the growth of the golden mussel as a function of the time of bioinfestation) and an analysis of the dimensions (length and height) of a sample of available mussels were carried out. in the lab. It was also analyzed, in the field, the fixation preference (in terms of the choice of materials arranged) and the interference of the fixation depth. These data were used to calculate the roughness, generated by mussel biofouling in the pumping suction and discharge piping, necessary to determine the loss of energy efficiency (head loss, energy consumption and pumping cost). The methods were applied to a pumping station representative of the Brazilian Amazon, as a case study. The results show an average increase in economic indicators (consumption and pumping cost) after the system suffers bioinfestation. This total increase corresponded to 19% and 44% in the first and second years, respectively, reaching the stabilization of the pumping cost increase in 46%, in the 30 months of operation. Our results demonstrate the pioneering nature of the proposal, as these are the first quantitative data on the energy efficiency of pumping associated with bioinfestation by the golden mussel and evolution of the load loss factor. These results can also be used to estimate the cost increase caused by golden mussel bioinfestation in the raw water pumping systems of other facilities.